Investigating Linguistically Diverse Adolescents' Literacy Trajectories Using Latent Transition Modeling. Issue 1 (8th July 2018) - Sinclair, Jeanne; Jang, Eunice Eunhee; Vincett, Megan
Abstract: This study examined the literacy profiles of students from diverse home‐language backgrounds and tracked those profiles from grade 6 to grade 10. The authors also investigated the predictive relations of students' immigration background, gender, and participation in two instructional programs. The results from latent class and latent transition analyses suggest that grade 6 literacy profiles are strong predictors of literacy profiles in grade 10. Students from diverse home‐language backgrounds and those who had immigrated to Canada tended to have strong literacy profiles and positive trajectories. The analyses also indicate that students who used very little or no English at home, even those who had a strong literacy skill profile in grade 6, may benefit from additional literacy support in high school. In terms of instructional programming variables, participation in an English as a Second Language program was associated with little change in students' literacy profiles over time, and career‐oriented streaming showed a strong negative impact on literacy skill development. In terms of language‐in‐education policy and practice, the findings support the idea that, generally speaking, students from multilingual home‐language environments retain strong literacy profiles between elementary and high school. The findings also emphasize the importance of quality instructional programming.